(untitled) (Third Sector Social Economic Review, 2017)
Cooperatives are social-economic organizations, which contribute economic, social, and environmental sustainability. Although the cooperative system in our country is quite old, it is inadequate compared to other countries. In this study, Gödence Rural Development Cooperative; which has 150 members, engaged in production and marketing of olive-olive oil and located in Gödence village in Seferihisar district, İzmir; and its contributions to regional development and innovations to its members and satisfaction and benefits with the cooperative services of the members are examined. The main population of this study constituted from Gödence Rural Development Cooperative members, which are residents of Seferihisar in İzmir province. Proportional sampling method formula is used to calculate sampling size. According to the proportional sampling method, with a 90% confidence interval and 10% margin of error, the required sample size was found to be 50. The opinions of members are approached by using average percentage calculations and Likert type-scale. The normal distribution test was done with the Kolmogorov-Smirnov test for continuous variables. It was determined that the variables did not show normal distribution. Mann-Whitney U test and Kruskal-Wallis test were applied for the variables. It was determined that the cooperative members are generally satisfied with the cooperative management (average: 3,60 std. deviation: 0,642). Cooperative members are not satisfied with the technical support(average: 1,79 std. deviation: 0,436). It was determined that the cooperative members are generally satisfied with cooperative marketing and sales activities (average: 3,96 std. deviation: 0,439).